Modeling of the Hybrid Vibration-based Energy Harvester for Self-Powered IoT Sensor - Ahmad, M.R. (Institute of Electrical and Electronics Engineers Inc., 2021)
Wireless sensor nodes (WSN) are usually used for the bridge monitoring system. The traditional way to supply power to these wireless sensor nodes by using the battery should be eliminated due to their disadvantages in terms of environmental health. Thus, an energy harvesting system has attracted interests among researchers due to its sustainability. Among all renewable energies, vibration energy is the most preferable energy for the application of the bridge sensor. Vibration energy consists of four transduction mechanisms which are piezoelectric, electromagnetic, electrostatic and magnetostrictive. In this paper, vibration energy harvesting is discussed by focusing on the hybrid energy harvester through the combination of piezoelectric and magnetostrictive transduction to enhance the output performance of the system. Hybrid structure based on piezoelectric and magnetostrictive mechanisms will be investigated in detail by focusing on their structure and the material to achieve the optimum output power than the conventional energy harvester. The spiral rectangular beam is designed and simulated by using the ANSYS software to get their resonance frequency value and frequency response for the beam. Simulation results show that the spiral rectangular design and lead zirconate titanate (PZT-5A) material proved promising results to obtain the optimum output power. For the magnetostrictive part, the ferromagnetic material has been replaced with the beryllium copper. Thus, distance of the magnet plays an important role for the optimum output power due to the presence of the magnetic flux density. Â© 2021 IEEE.